Selection of location of fuel pressure sensors for registration of oscillatory process - Булгаков, Николай Петрович; Зенкин, Евгений Юрьевич (Technology audit and production reserves, 2015)
Due to the deterioration in the fuel quality, more drivers are turning to service centers for rehabilitation of the fuel system. It is necessary to develop a method of diagnosis of these systems, which allows for a minimum of material costs get the maximum amount of information about the tested system. It was conducted a study on the selection of pressure sensors and their location on the fuel injection system of the vehicle for the diagnosis of the fuel equipment. It was conducted an experiment using two different types of sensors and two cars with different design of the fuel system. The pressure oscillograms were obtained simultaneously with the recorded signals of nozzle control, current strength at the nozzle and air flow. It was concluded that these sensors may be used to diagnose the gasoline systems with the fuel injection on the valve.